Comparison Between Actigraphy Records and Parental Reports of Child's Sleep - Perpétuo, Catarina; Fernandes, Marília; Veríssimo, Manuela (Frontiers in Pediatrics, 2020)
Given the impact of sleep in several domains of a child's development, the comparison between actigraphic and parental questionnaires is of great importance in preschool age, an understudied age group. While parental reports tend to overestimate sleep duration, actigraphy can increase the frequency of night-wakings. Our primary goal was to compare actigraphy data and parental reports (Children’s Sleep Habits Questionnaire, CSHQ), regarding bedtime, wake-up time, sleep duration and wake after sleep onset (WASO), using Bland-Altman technique. Forty-six children, aged between 3 and 6 years and their parents participated. Results suggest that, despite of existing associations between sleep schedule variables by both methods (from r = .57 regarding bedtime at weekends to r = .86 regarding wake-up time during the week, ps), differences between them were significant and agreements were weak, given that parents overestimate bedtimes and wake-up times in relation to actigraphs. Differences between actigraphy and CSHQ were ±52 minutes for weekly bedtime, ±38 minutes for weekly wake-up time, and ±159 minutes for total sleep time and ±62 minutes for WASO, indicating unsatisfactory agreement between methods. Our study contributes to the knowledge of the characteristics of each instrument, along with their tendency to over and underestimate certain sleep parameters. We conclude that a complementary use of both instruments should better inform clinical practice and research on child's sleep